Orthographic Hypercorrection Using Accent Marks in Academic and Informative Documents in Costa Rica - Tomcsányi Major, Judit (2015)
This paper examines data of a special kind of misuse of orthographic accent in Spanish, namely its abusive or dislocated application in certain types of texts in Costa Rica. From the perspective of phonological analysis (Harris) in the frame of metrical theory, and of psycholinguistic research on written word processing (Frost, Taft) we argue that this type of hypercorrection is due to lexical processing, typically related to deep orthographies, leaving aside the basically transparent nature of Spanish orthography. A specific orientation of this lexical processing to accent markedness is identified suggesting a particular conception users have of orthography.